Targeted mutation of barley (1, 3;1, 4)‐β‐glucan synthases reveals complex relationships between the storage and cell wall polysaccharide content. (29th September 2020) - Garcia‐Gimenez, Guillermo; Barakate, Abdellah; Smith, Pauline; Stephens, Jennifer; Khor, Shi F.; Doblin, Monika S.; Hao, Pengfei; Bacic, Antony; Fincher, Geoffrey B.; Burton, Rachel A.; Waugh, Robbie; Tucker, Matthew R.; et al.
SUMMARY: Barley ( Hordeum vulgare L) grain is comparatively rich in (1, 3;1, 4)‐β‐glucan, a source of fermentable dietary fibre that protects against various human health conditions. However, low grain (1, 3;1, 4)‐β‐glucan content is preferred for brewing and distilling. We took a reverse genetics approach, using CRISPR/Cas9 to generate mutations in members of the Cellulose synthase‐like ( Csl ) gene superfamily that encode known ( HvCslF6 and HvCslH1 ) and putative ( HvCslF3 and HvCslF9 ) (1, 3;1, 4)‐β‐glucan synthases. Resultant mutations ranged from single amino acid (aa) substitutions to frameshift mutations causing premature stop codons, and led to specific differences in grain morphology, composition and (1, 3;1, 4)‐β‐glucan content. (1, 3;1, 4)‐β‐Glucan was absent in the grain of cslf6 knockout lines, whereas cslf9 knockout lines had similar (1, 3;1, 4)‐β‐glucan content to wild‐type (WT). However, cslf9 mutants showed changes in the abundance of other cell‐wall‐related monosaccharides compared with WT. Thousand grain weight (TGW), grain length, width and surface area were altered in cslf6 knockouts, and to a lesser extent TGW in cslf9 knockouts . cslf3 and cslh1 mutants had no effect on grain (1, 3;1, 4)‐β‐glucan content. Our data indicate that multiple members of the CslF / H family fulfil important functions during grain development but, with the exception of HvCslF6, do not impact the abundance of (1, 3;1, 4)‐β‐glucan in mature grain. Significance Statement: We used CRISPR/Cas9 to edit several Cellulose synthase‐like (Csl) genes ( HvCslF3, HvCslF6 HvCsl9 and HvCslH ). We characterised grain composition of these mutant lines. This is the first time that stable knockouts have been generated for CslF9 . Intriguingly, our analysis of HvCslF9 mutant lines suggests it has a distinct role in determining grain composition. The lines generated of these genes, HvCslF3 and HvCslH, provide a catalogue of mutants that will facilitate the study of the plant cell wall.